'We never thought this would be considered drug trafficking': International finance rules, policy space and Uruguay's regulation of recreational cannabis - Rachel Ann Barry (Taylor & Francis Group, 2023)
ABSTRACTFollowing landmark legislation in 2013, Uruguay became the first country to regulate the legal production, distribution and sale of recreational cannabis. While broader debates anticipated the significance of the UN drug conventions, the extent to which Uruguay's drug treaty obligations shaped regulation is unclear and the relevance of finance norms has been neglected. Drawing on institutionalist and governance theories, this study explores how international drug and finance regulations limited Uruguay's policy space to implement cannabis regulation, and how this was perceived by policy actors. Policy documents and 43 semi-structured interviews were thematically analysed. The analysis demonstrates how Uruguay's drug treaty obligations were less directly constraining to policy space compared to international finance norms, including the US Patriot Act, anti-money laundering standards and financial inclusion practices. Such norms exerted powerful influence over Uruguay's ability to implement aspects of cannabis supply that interact with broader financial systems, allowing banks to terminate business relationships with clients deemed as high risks for money laundering. The Uruguayan case suggests that financial regulations at diverse levels are likely to constrain policy space in other contexts where the market-based policies of cannabis regulation raise tensions with a narrowly constructed risk management principle in approaches to financial supply.